AQUACULTURE ADVANCEMENT IN BIOTECHNOLOGY: REVIEW - IGBANI FLOURIZEL,; Akpevwe, Okere Efe; Osijaye, Gabriel Kingdom (International Journal For Research In Agricultural And Food Science, 2023)
Population blast, anthropogenic activities and climate change have caused first class protein like fish to be limited to consumers; the cost of fish flesh proteins are on the increase due to environmental pollution and overfishing has made capture fisheries a nightmare; this gave birth to fish farming/aquaculture and aquaculture advancement in biotechnology. This article reviews aquaculture advancement in genetic engineering/hybridization improvement and biotechnology. Fish farmers should be exposed to primary genetics/hybridization/biotechnology principles; practical skills of hybridization/biotechnology be demonstrated to fisheries and aquaculture undergraduates and farmers. Biotechnology engineering is the way forward for fish protein multiplication, disease resistant fish breeds and high fecundity which farmers need to embrace. A lot of persons have talked down on genetics/biotechnology engineering in fish production but it is a sure way for food security in Africa and the globe at large not forgetting the building of genetics: natural selection in animal husbandry.